Analisis DU PONT SYSTEM dan Economic Value Added Pada PT. Kimia Farma dan PT. Indofarma - Melinda Ibrahim (Jurnal Ekonomi dan Manajemen, 2018)
This study aims to assess the company's financial performance using the analysis of Du Pont System and Economic Value Added (EVA). Sampling was carried out by simple random sampling method with financial data for three periods, namely 2014-2016. This research is a descriptive study with a quantitative approach. The results showed that PT. Kimia Farma Tbk in the calculation of Return On Investment there is a fluctuation. This shows that the company earns a profit and in accordance with the industry average standards, while PT. Indofarma Tbk tends to decline and is below the industry standard average. This condition shows that the company is less effective in managing assets and controlling the expenses incurred by the company. In the EVA analysis, PT Kimia Farma Tbk and PT Indofarma Tbk for three periods, namely 2014-2016, obtained information that the company gained economic added value every period that continued to increase. This certainly attracts investors to invest in PT. Kimia Farma Tbk and PT. Indofarma Tbk